Stakeholder Perspectives of the Inflation Reduction Act's (2022) Impact on Prescription Drugs: A Narrative Review - Cristian Lieneck; Matthew McLauchlan; Valerie Adachi; Roger Billings (MDPI AG, 2023)
In this review, we examine the impact of the Inflation Reduction Act (IRA) of 2022 on pharmaceutical drugs in the United States, drawing on a diverse range of sources to understand the perceptions of multiple stakeholders and professionals. Findings suggest that the Act, while aiming to control price inflation, has had a multifaceted impact on the pharmaceutical sector. Stakeholders, including pharmaceutical companies, healthcare providers, patient advocacy groups, and policymakers, offered varied perspectives: while some laud the Act for its potential in controlling runaway drug prices and making healthcare more accessible, others raise concerns about possible reductions in drug innovation, disruptions to supply chains, and the sustainability of smaller pharmaceutical companies. The review identified four underlying constructs (themes) in the literature surrounding healthcare stakeholders' perceptions of the IRA's impact upon prescription drugs: pricing and/or dictation pricing issues, topics related to patent law and pharmaceuticals, processes surrounding the IRA's (2022) rules and regulations, and potential threats to the pharmaceutical industry concerning the research and development of future medications. The complex interplay of the Act's implications underscores the importance of ongoing assessment and potential iterative policy refinements as implementation endures.